Retrospeksi kebijakan pangan dan implikasinya terhadap upaya memenuhi pola pangan harapan - Unggul Priyadi (Universitas Islam Indonesia, 2001)
The food policy applied by government is focused on the increase of rice. One achievement of the policy establishment is the rice swasembada in 1984. However, after that rice production decrease while other food commodities do not have enough support from government.